Kewarganegaraan Hak – hak Perdata : Analisis Perbandingan antara Warga Negara dan bukan Warga Negara - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Azmi Fauziyah; Rizki Anafis; Yusna Kamila Firdausi (International Forum of Researchers and Lecturers, 2024)
This study explores the comparative analysis of civil rights between citizens and non-citizens, examining various regulations and their implementation in different countries. Citizenship often determines an individual's access to various civil rights, such as property ownership, access to justice, and contract rights. These differences in treatment can create injustices and discrimination against non-citizens. The study employs a normative legal approach with comparative and case study methodologies, focusing on regulations in Indonesia, the United States, Germany, and Japan. The findings reveal that in Indonesia, non-citizens face restrictions on property ownership, while in the United States and Japan, although regulations are more flexible, there are still limitations related to strategic or sensitive properties. In Germany, immigrants and asylum seekers often encounter greater legal barriers to accessing justice. Conversely, in countries like the United Kingdom and the United States, although there are no formal restrictions on contracts for non-citizens, they may face practical difficulties in accessing the necessary services to fulfill contractual obligations. The study recommends the need for more inclusive legal reforms to reduce inequalities and discrimination, and to enhance access to justice and civil rights for non-citizens. Additionally, strengthening legal aid services and international cooperation in civil law are suggested to ensure fair protection of rights for all individuals. The findings contribute significantly to the international civil law literature and provide valuable insights for policymakers in developing more equitable and sustainable policies in the era of globalization.